2015
DOI: 10.1111/mec.13038
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence of geographically widespread effect of gene flow from polar bears into brown bears

Abstract: Polar bears are an arctic, marine adapted species that is closely related to brown bears. Genome analyses have shown that polar bears are distinct and genetically homogeneous in comparison to brown bears. However, these analyses have also revealed a remarkable episode of polar bear gene flow into the population of brown bears that colonized the Admiralty, Baranof and Chichagof islands (ABC islands) of Alaska. Here, we present an analysis of data from a large panel of polar bear and brown bear genomes that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(203 citation statements)
references
References 54 publications
12
187
4
Order By: Relevance
“…There is an emerging consensus that gene flow frequently occurs following speciation despite the establishment of reproductive barriers that otherwise maintain species-level distinctiveness (Roca et al 2005;Good et al 2008;Ellegren et al 2012;Garrigan et al 2012;Toews and Brelsford 2012;Cahill et al 2013Cahill et al , 2014Cui et al 2013;Martin et al 2013;Kutschera et al 2014;Sullivan et al 2014). However, incomplete lineage sorting (ILS) is assumed by default to underpin most cases of phylogenetic discordance.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 2 more Smart Citations
“…There is an emerging consensus that gene flow frequently occurs following speciation despite the establishment of reproductive barriers that otherwise maintain species-level distinctiveness (Roca et al 2005;Good et al 2008;Ellegren et al 2012;Garrigan et al 2012;Toews and Brelsford 2012;Cahill et al 2013Cahill et al , 2014Cui et al 2013;Martin et al 2013;Kutschera et al 2014;Sullivan et al 2014). However, incomplete lineage sorting (ILS) is assumed by default to underpin most cases of phylogenetic discordance.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…However, incomplete lineage sorting (ILS) is assumed by default to underpin most cases of phylogenetic discordance. Few studies in the literature account for hybridization by analyzing all inheritance patterns (uniparental, sex-biased, biparental) with high-resolution data, or instead have focused on only a few species (Roca et al 2005;Cahill et al 2013Cahill et al , 2014Trigo et al 2013;Khan et al 2014). The cat family Felidae contains 38 recognized species within eight lineages (designated henceforth by a capitalized name, e.g., Puma lineage) that vary in the breadth of their geographic occurrence (Buckley-Beason et al 2006;Johnson et al 2006).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation
“…Male gene flow has subsequently diluted the original insular polar bear alleles, with higher swamping (lower percentage of polar bear alleles remaining) at loci that show a malebiased inheritance (autosomal > X > mtDNA) (Cahill et al 2013). As subsequently shown by Cahill et al (2015) who sequenced two additional ABC-Island and one European brown bear, brown bears have effectively acted as vectors for polar bear alleles (Hailer 2015): malebiased dispersal by brown bears has carried introgressed polar bear alleles far away from the original zone of admixture into brown bear populations resident on the adjacent North American mainland Liu et al (2014) reported the deep sequencing and de novo assembly of another polar bear genome. The authors used allele frequency and linkage information from 89 sequenced bear genomes for an in-depth demographic modelling of polar/brown bear evolutionary history [see next section for details on aspects of genomic adaptation signals].…”
Section: Discovery Of a Pleistocene Polar Bear Jawbone Stimulates Newmentioning
confidence: 94%
“…The significant D-statistics varied from 0.07 to 0.17, which is slightly higher compared to analyses on recent radiations, such as Darwin's Finches (0.004 -0.092; Lamichhaney et al, 2015) and butterflies of the genera Heliconius (0.04; Dasmahapatra et al, 2012) and Papilio (0.04; Zhang et al, 2013). These values do fall within the range of studies on other hybridizing species, such as pigs (0.11 -0.23; Frantz et al, 2013), bears (0.04 -0.46; Liu et al, 2014, Cahill et al, 2015 and Xiphophorus fish (0.03 -0.56; Cui et al, 2013). A significant D-statistic does not necessarily indicate introgression between the species from which the genomes are being compared.…”
Section: General Patterns Of Introgressionmentioning
confidence: 53%